Performance of newly developed sunflower inbred lines for yield and yield contributing traits under rainfed condition: Performance of newly developed sunflower inbred lines for yield and yield contributing traits under rainfed condition - D MOHAN VAMSI; G SANDHYASREE; H P MEENA; S K PAYASI; A VISHNUVARDHAN REDDY (Journal of Oilseeds Research, 2020)
The present investigation was carried out at ICAR-Indian Institute of Oilseeds Research, Hyderabad. The material consisted of 25 newly developed mono and multi headed restorer lines. The data for agronomic and yield traits was recorded. The genotypes, COSF-6B, COSF-7B, RGP-11-P1-S2, RGP-58-P4-S1-1 and RGP-46-P3 were identified as the most important genotypes for different traits and should be utilized in hybridization program to realize high heterosis for yield and yield contributing traits.